Technological advancements towards the net-zero energy communities: A review on 23 case studies around the globe. (August 2021) - Ullah, K.R.; Prodanovic, V.; Pignatta, G.; Deletic, A.; Santamouris, M.
Abstract: "Net-zero energy", a burning concept of the current world, has been being considered and applied on a building scale for the last few decades, however, there are significant advantages to moving to the community level. This study identifies the technological advancements of net-zero energy communities through in-depth literature review study. 23 case study settlements have been identified and analyzed based on their design methodology along with some practical applications around the globe. The focus of this work is on technologies and measures utilized for the reduction of energy consumption, minimization of greenhouse gas (GHG) emissions, and the generation of electrical and thermal energy by renewables. We identified different mitigation strategies adopted for outdoor heat sources, building adaptation techniques, and renewable energy technologies along with control strategies. The study reveals that all the settlements mainly focus on the onsite energy generation, while 17 settlements among them, additionally, consider various adaptation techniques that have significantly lessened the energy demand of the buildings. A few studies (4 settlements only) incorporate some mitigation strategies to mitigate the outdoor heat sources that enable to lower the ambient temperature along with diminishing the GHGs emissions as well as minimizing the energy demand of the community. In addition, the climate zones have significant impacts on selecting the building adaptation tools and measures. Alongside the energy balance, we have also epitomized the effects of various energy management and control strategies adopted for the smooth operation of energy. Finally, we shed light on the problems and challenges of existing net-zero energy settlements and make recommendations by considering the environment, energy, and economy towards achieving the net-zero energy purpose at the community level.